A trajectory of dissemination of ideas of public choice (Revista do Serviço Público, 2021)
The biographies of intellectuals who, throughout their lives, are dedicated to making known a set of ideas that they deem important for society are getting increasingly rare. An analysis of Professor Jorge Vianna Monteiro's curriculum shows an academic who has consistently dedicated himself to the study, research, and dissemination of the contents of a school of thought –public choice – that has profoundly influenced the studies of economics, political science, and  public management in recent decades.